2019
DOI: 10.1021/acs.jmedchem.9b00550
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Study of Antimicrobial Auranofin against ESKAPE Pathogens

Abstract: Auranofin, an FDA-approved arthritis drug, has recently been repurposed as a potential antimicrobial agent; it performed well against many Gram-positive bacteria, including multidrug resistant strains. It is, however, inactive toward Gram-negative bacteria, for which we are in dire need of new therapies. In this work, 40 auranofin analogues were synthesized by varying the structures of the thiol and phosphine ligands, and their activities were tested against ESKAPE pathogens. The study identified compounds tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 79 publications
6
73
0
Order By: Relevance
“…Shi et al have reported that ferulic acid and ferulic acid alkyl esters (FAC2) with 1.4212 and 2.1762 of Clog P values showed higher antibacterial activity against E. coli as compared with other similar compounds having higher Clog P values (Shi et al, 2018). Moreover, this similar trend also was reported by Wu et al They found auranofin analogs with lower log P values (1–2) exhibited better activity than some analogs with higher log P values (>3) against S. aureus, E. coli , and P. aeruginosa (Wu et al, 2019). In view of the results, we can suggest that high hydrophobicity promotes reagents uptake by bacteria because of the lower Clog P value.…”
Section: Resultssupporting
confidence: 82%
“…Shi et al have reported that ferulic acid and ferulic acid alkyl esters (FAC2) with 1.4212 and 2.1762 of Clog P values showed higher antibacterial activity against E. coli as compared with other similar compounds having higher Clog P values (Shi et al, 2018). Moreover, this similar trend also was reported by Wu et al They found auranofin analogs with lower log P values (1–2) exhibited better activity than some analogs with higher log P values (>3) against S. aureus, E. coli , and P. aeruginosa (Wu et al, 2019). In view of the results, we can suggest that high hydrophobicity promotes reagents uptake by bacteria because of the lower Clog P value.…”
Section: Resultssupporting
confidence: 82%
“…The group of Yan prepared 40 auranofin analogues to determine their Gram(+), Gram(−), and cytotoxic activity, establishing a structure-activity relationship. Compounds (1-4) possessed a broader activity spectrum, with bactericidal activity against S. aureus, A. baumannii, Enterobacter cloacae, E faecium, and E. coli, with associated half maximal inhibitory concentration (IC 50 ) values between 50 and 100 µM against A549 cells (Table 1) [16]. For the Gram(+) bacteria tested, the cytotoxicity was around two orders of magnitude lower than the antibacterial activity, indicating a favorable therapeutic index.…”
Section: Galliummentioning
confidence: 99%
“…As the longer chain length leads to more lipophilic compounds, the authors concluded that this increase in lipophilicity is responsible for the higher uptake [86]. Later studies showed that 10 16 preferentially binds RNA in live bacteria and accumulates at the ribosomes, condensing them when they form polysomes. This finding suggests that the compounds halt translation of RNA and thereby protein synthesis in bacteria [87].…”
Section: Rutheniummentioning
confidence: 99%
See 1 more Smart Citation
“…Auranofin is an anti‐arthritic drug and has been re‐purposed for antimicrobial activity. Auranofin showed activity against gram‐positive bacteria but had almost no effect against the gram‐negative ones [77] . To alter this, a number of auranofin analogues were generated by varying their thiol and phosphine functionalities and their antimicrobial activities were studied against ESKAPE pathogens (Figure 30).…”
Section: Bio‐medical Applicationsmentioning
confidence: 99%